Happy birthday, Thomas! - Awdry, W. Rev; Bell, Owain; Awdry, W. (New York : Random House, 2003)
Thomas the train engine thinks that all the other engines are too busy to help him celebrate his birthday, but he is in for a surprise.
"Thomas & friends"--Cover.
Preschool-1.
Keywords: Birthdays -- Fiction; Parties -- Fiction; Railroads -- Trains -- Fiction